2021
DOI: 10.1007/s12325-021-01790-y
|View full text |Cite
|
Sign up to set email alerts
|

Disease Behaviour During the Peri-Diagnostic Period in Patients with Suspected Interstitial Lung Disease: The STARLINER Study

Abstract: Introduction Disease behaviour may guide diagnosis and treatment decisions in patients with interstitial lung disease (ILD). STARLINER aimed to characterise disease behaviour in patients with suspected ILD during the peri-diagnostic period using real-time home-based assessments. Methods STARLINER (NCT03261037) was an international, multicentre study. Patients ≥ 50 years old with suspected ILD were followed throughout the peri-diagnostic period, consisting of a pre-diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Table 1 shows the characteristics of the included studies. Of the 40 studies, 11 studies [ 9 , 21 , 34 , 35 , 37 , 46 , 49 – 52 , 58 ] were intervention studies, 13 studies [ 3 , 7 , 8 , 22 , 29 , 30 , 33 , 36 , 41 , 43 , 47 , 54 , 56 ] were cohort studies and 16 studies [ 4 , 5 , 10 , 31 , 32 , 38 40 , 42 , 44 , 45 , 48 , 53 , 55 , 57 , 59 ] were cross-sectional studies. Of the 16 cross-sectional studies, one was a validation study of a PA questionnaire [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows the characteristics of the included studies. Of the 40 studies, 11 studies [ 9 , 21 , 34 , 35 , 37 , 46 , 49 – 52 , 58 ] were intervention studies, 13 studies [ 3 , 7 , 8 , 22 , 29 , 30 , 33 , 36 , 41 , 43 , 47 , 54 , 56 ] were cohort studies and 16 studies [ 4 , 5 , 10 , 31 , 32 , 38 40 , 42 , 44 , 45 , 48 , 53 , 55 , 57 , 59 ] were cross-sectional studies. Of the 16 cross-sectional studies, one was a validation study of a PA questionnaire [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…15 studies included patients with ILD due to any causes [ 8 , 21 , 30 34 , 37 , 46 48 , 51 , 53 , 55 , 59 ], 15 studies included only idiopathic pulmonary fibrosis (IPF) [ 5 , 7 , 9 , 22 , 29 , 40 43 , 45 , 49 , 50 , 54 , 56 , 58 ], seven studies included only sarcoidosis [ 4 , 35 , 36 , 38 , 39 , 52 , 57 ] and three studies included another ILD subtype [ 3 , 10 , 44 ]. The total sample size of each study ranged from 13 [ 46 ] to 629 [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single centre studies have shown that data acquired from home is reliable when compared with hospital spirometry [82][83][84]. However, multicentre studies have reported problems with implausible outliers, long-term missing data, and weak correlations between longitudinal patterns in home and hospital spirometry [85,86]. Artificial intelligence may help in developing algorithms to standardise acceptability and usability of the spirometric manoeuvre and deliver real-time automated feedback to patients [87].…”
Section: Current Knowledge About Ehealth In Pfmentioning
confidence: 99%
“…The first studies, in patients with IPF, used paper diaries to collect home spirometry results, which hampers use in clinical practice [ 18 , 20 ]. Moreover, some studies encountered technical problems, such as connection issues with the spirometers, and large variability of the data [ 21 ▪▪ , 22 ]. Many of these problems can be overcome by using the IoMT.…”
Section: Online Home Monitoringmentioning
confidence: 99%